Investigating alternative educational punishments to imprisonment and its impact on the family (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, while presenting the concept of alternative educational punishments to imprisonment, we try to examine the evolution of imprisonment. Historical studies of human life have shown the occurrence of various crimes in society, which have endangered the order and security of society. Experience has shown that when a person commits a crime and delinquency, society reacts to the crime and punishes the perpetrator in order to preserve the values ​​and norms of society. In earlier societies, most punishments and social reactions to crime and delinquency were physical, violent, and inhumane. Also, these punishments were carried out in public with the aim of correction, lessons and intimidation of the public. Imprisonment was rarely used and was often carried out in pre-trial form. This practice continued until the beginning of the twelfth century AD, when over time the practices and behaviors that led to the punishment of imprisonment increased in societies, until it reached its peak in the late sixteenth and seventeenth centuries. Nearly a century of imprisonment has been the main punishment in most countries, with the main goal of correcting, punishing, educating the offender and returning him to the community. However, during this period, this punishment not only failed to rehabilitate prisoners and criminals, but also had negative consequences for criminals and even their families. One of these consequences is that the offender loses irreparable opportunities in terms of work, education and family formation. Such people are often disrespected by society, which is rejected by the family. The criminal population of prisons was increasing day by day. Until the beginning of the twentieth century, the school of social defense, led by Mark Ansel, strongly opposed the punishment of imprisonment, especially short-term imprisonment, and its proponents proposed alternative punishments instead of imprisonment. Due to the fact that these people commit various crimes for various reasons, and are sentenced to various punishments and are sent to prisons, they incur high costs for the society and cause them to lose the opportunity to return to the society successfully. Therefore, with the establishment of alternative educational punishments to imprisonment, in the legal system, in addition to having a significant effect on reducing costs, the rehabilitation of the delinquent personality in this system is better and returns to the community by performing public services to correct him.